2008
DOI: 10.1002/marc.200800435
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Route to Organic–Inorganic Hybrid Nanomaterials

Abstract: In the present work, the application of electron‐deficient tetraphenylporphyrinatovanadium(IV) trifluoromethanesulfonate, [VIV(TPP)(OTf)2], in the trimethylsilylation of alcohols and phenols with hexamethydisilazane (HMDS) is reported. This new V(IV) catalyst was used as an efficient catalyst for silylation of not only primary alcohols but also sterically hindered secondary and tertiary alcohols with HMDS. Trimethylsilylation of phenols with HMDS was also performed to afford the desired Trimethylsilyl ethers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 70 publications
0
29
0
Order By: Relevance
“…It has been reported that monomers with a single trialkoxysilyl group segregate to the surface of particles during polymerizations 46), 47) and bridged monomers with two trialkoxysilyl groups are more homogeneously distributed. 48) Dansyl amides experience a substantial bathochromic shift in fluorescence emission maximum with increasing solvent polarity making them useful in probing materials' microenvironments.…”
Section: Covalent Encapsulation Of 2 and 3 Viamentioning
confidence: 99%
“…It has been reported that monomers with a single trialkoxysilyl group segregate to the surface of particles during polymerizations 46), 47) and bridged monomers with two trialkoxysilyl groups are more homogeneously distributed. 48) Dansyl amides experience a substantial bathochromic shift in fluorescence emission maximum with increasing solvent polarity making them useful in probing materials' microenvironments.…”
Section: Covalent Encapsulation Of 2 and 3 Viamentioning
confidence: 99%
“…Due to the living character of CRP techniques, it is possible to continue the polymerization with a second monomer after consumption of the first monomer, which leads to block copolymer-grafted silica nanoparticles. 138,148 Correspondingly, the number-average molecular weight (Mn) of grafted PSt is 3.6, 6.2, 8.9, 12.0, 14.3, and 15.4 kg/mol, respectively. The images of the PSt silica nanohybrids show micrometer-sized polymer film domains containing a monolayer of silica nanoparticles.…”
Section: Page 8 Of 48 Polymer Chemistrymentioning
confidence: 99%
“…95,137,147,178,179 Additionally, free polymers produced by the sacrificial free initiator form an entangled network structure which prevents nanoparticle diffusion, diminishes interparticle coupling, and avoids gelation or aggregation. 95,137,147,178,179 Up to now, utilizing surface-initiated ATRP, various synthetic polymers such as PSt, 41,138,148,161,162 PMMA, 139,147,148,162,177 poly(n-butyl acrylate) (PnButA), 94 142 as well as polyelectrolytes 142,151,[163][164][165] have been grafted from silica nanoparticles (Table 1). Due to the living character of CRP techniques, it is possible to continue the polymerization with a second monomer after consumption of the first monomer, which leads to block copolymer-grafted silica nanoparticles.…”
Section: Page 8 Of 48 Polymer Chemistrymentioning
confidence: 99%
“…Synthesis and properties of inorganic-organic hybrid materials have attracted much attention due to their potential applications in many fields involving materials science and biotechnique [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Among them, silica particles are solid supports of choice to construct the target hybrids due to their excellent mechanical stability, low costs and variable particle sizes and specific surface area [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%